Pengaruh Citra Merek Dan Harga Terhadap Keputusan Pembelian Produk Mustika Ratu Pada Pegawai Rumah Sakit Bunda Pengharapan - Simon Siamsa (Musamus University, Merauke Papua Indonesia., 2019)
Research objectives To know the influence of brand image to buy product decisions Mustika Ratu in the employee hospital mothers Hope. Methods with a quantitative approach. Population and samples of 30 respondents using saturated sampling techniques and data analysis techniques: Simple regression assisted by SPSS. The results showed that the brand image of the t value is greater than t table that is 2.582> 1.703 and the value of sig, 016 because sig smaller 0.05 results show brand image has a positive and significant effect on purchasing decisions, while for the price variable t value greater than t table is 2.329> 1.703 and sig 0.028 smaller than 0.05 indicates that the price variables have a positive and significant effect on purchasing decisions. Keywords: brand image, price, purchasing decisions.